ETHNOBOTANICAL STUDY OF PLANTS USED TO TREAT ASTHMA IN THE MARITIME REGION IN TOGO - Gbekley, Holaly E.; Katawa, Gnatoulma; Karou, Simplice D.; Karou, Simplice D.; Anani, Kokou; Tchadjobo, Tchacondo; Ameyapoh, Yaovi; Batawila, Komlan; Simpore, Jacques (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Asthma is one of the most common chronic diseases in modern society and it is evident that its incidence and severity are increasing, however very little is known about the plants used in the management of the disease. This study therefore aimed to document the plants usage in the Togolese traditional medicine to treat asthma. Methodology: From January to June 2015, an ethnobotanical survey was conducted using a semi-structured questionnaire with traditional healers (THs) in the southern region of Togo. The importance of the plants species was assessed by the calculated use values. Results: In Total, 121 THs (92 males and 29 females) were interviewed and 98 plants species belonging to 54 families were identified as curing asthma. The most represented families were: Leguminosae with 7 species followed by Euphorbiaceae and Rutaceae contributing with 6 and 5 species respectively. Based on the calculated use values the most important species were Carcica papaya L., Cataranthus roseus L., Eucalyptus camaldulensis Dehnh., Piper guineense Thonn., Eucalyptus citriodora Hook., Eucalyptus globules Labill. and Euphorbia hirta L. The leaves and the root were the parts predominantly used to prepare the formulations, mainly decoctions, administrated by oral route. Clinical manifestations such as wheezing (91.74%), difficulty as speaking or coughing (73.55%), dyspnea (66.94%), dry cough (52.89%), sweating and increased heart rate (52.07%) were used by TH to diagnose the disease. Conclusion: This study showed initial evidence of the use of plant materials by Togolese TH to heal asthma. These results could be a starting point for laboratory screenings.